The Religious Cosmology of Indigenous Communities for Maintaining Ecological Balance in the Mentawai Islands, Indonesia - Wahyuni, Dwi; Octavia, Indah Andika; Karista, Karen; Sabna, Anjali; Martalia, Martalia (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This research aims to explore how the belief systems of indigenous peoples influence everyday conservation practices and examine how these beliefs can be integrated into modern conservation policies. This study employed an ethnographic qualitative approach. Data collection involved participatory observation, enabling involvement in daily life to directly observe community interactions with the environment and the performance of religious rituals. In-depth interviews were administered semistructured interviews with various key informants, including traditional leaders, religious figures, community elders, and environmental practitioners. Secondary sources from academic publications, government reports, and media archives relevant to the research topic. Interpretative analysis was conducted within cultural and historical contexts to gain a deeper understanding of how religiosity shapes the environmental conservation practices of the Mentawai people. This study presents three key findings related to the environmental conservation practices of the Mentawai community. Their conservation practices are deeply rooted in a belief system. Transformative dynamic is observed, whereby the younger generation successfully combines traditional values of ancestral religion with teachings from world religions and modern perspectives. A gap is identified between the local wisdom-based conservation system and the pressures exerted by the global political economy. The study provides new insights into the crucial role of local religiosity in environmental conservation and highlights the potential for integrating traditional and modern beliefs in nature conservation efforts. The study suggests that environmental conservation strategies should integrate local communities' religious values and indigenous knowledge rather than relying solely on scientific and technological approaches.